SPECIFIC CHARACTERISTICS OF SPIRITUAL AND MORAL EDUCATION OF PRIMARY CLASS STUDENTS - Sabokhat USMONOVA (Scholar Express Journal, 2023)
In this article, the students ' spiritual and moral The factors of improvement of the specific characteristics of education have been theoretically analyzed. In addition , students moral – spiritual. It is determined in the educational conditions of the development of the spiritual and moral culture of students based on the improvement of their qualities and culture formation
Keywords: Spiritual and moral; culture; qualities